Mentaculus Laws and Metaphysics - Heather Demarest (Principia: An International Journal of Epistemology)
The laws of nature are central to our understanding of the world. And while there is often broad agreement about the technical formulations of the laws, there can be sharp disagreement about the metaphysical nature of the laws. For instance, the Newtonian laws of nature can be stated and analyzed by appealing to a set of possible worlds. Yet, some philosophers argue the worlds are mere notational devices, while others take them to be robust, concrete entities in their own right. In this paper, I use a recent view of laws called the Mentaculus as a case study to illustrate the wide variety of metaphysical pictures that can accompany such a view. I conclude that the technical features of the laws -- typically (though not always) given to us by practicing scientists -- are compatible with many different metaphysical foundations.